How do Anaesthetists in New Zealand Disseminate Critical Airway Information?. Issue 3 (May 2013) - Baker, P. A.; Moore, C. L.; Hopley, L.; Herzer, K. R.; Mark, L. J.
The communication of information concerning patients with difficult airways is universally recognised as an important component in avoiding future airway management difficulties. A range of options is available to impart this information; little is known however, about the follow-up patterns of anaesthetists following the identification and management of a difficult airway. In this study, 158 anaesthetists were contacted and asked to comment on their follow-up patterns regarding a number of difficult airway scenarios. This was followed by a retrospective survey of 124 patients with known difficult airways. A wide discrepancy was found between stated follow-up preferences by anaesthetists and the actual use of options such as postoperative visits, notes in the clinical record, letters to the patient and family doctor, and entries in hospital, national and MedicAlert™ databases. Of the patients with an airway difficulty noted on their anaesthetic record, only 14% of them also had a pertinent comment on their clinical record; even fewer were referred to hospital warning systems (12%) or national (6%) and MedicAlert (7%) databases. Comments from our survey were critical of multiple difficult airway databases and alert systems, which are not linked and do not lead automatically to a single source of information. We suggest that a custom-designed MedicAlert New Zealand difficult airway/intubation registry could be established, with easy access for medical practitioners and patients. This registry could be accessed through the National Health Index database and linked to the MedicAlert international registry and their nine international affiliates.